2011
DOI: 10.1189/jlb.0810464
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kγ controls leukocyte recruitment, tissue injury, and lethality in a model of graft-versus-host disease in mice

Abstract: PI(3)Kγ is thought to mediate leukocyte migration to injured tissues and may be important in the pathogenesis of various T-lymphocyte-dependent pathologies, including autoimmune and inflammatory diseases. The present study evaluated the relevance of PI(3)Kγ in donor cells for the pathogenesis of acute GVHD using a model of adoptive transfer of splenocytes from WT or PI(3)Kγ(-/-) C57BL/6J mice to B6D2F1 mice, and mice that received PI(3)Kγ(-/-) cells showed reduced clinical signs of disease, bacterial transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…The skeletal muscle tissue was removed and fixed in buffered formaldehyde (10% in PBS) for 24 hours and routinely processed for paraffin embedding. Sections (5-µm thick) were obtained and stained with H & E [18]. The images were captured using a microscope at a resolution of 720×480 pixels (Cool SNAP-Procf Color, Media Cybernetics, Bethesda, MD) and evaluated using the program Image ProExpress version 4.0 for Windows (Media Cybernetics).…”
Section: Methodsmentioning
confidence: 99%
“…The skeletal muscle tissue was removed and fixed in buffered formaldehyde (10% in PBS) for 24 hours and routinely processed for paraffin embedding. Sections (5-µm thick) were obtained and stained with H & E [18]. The images were captured using a microscope at a resolution of 720×480 pixels (Cool SNAP-Procf Color, Media Cybernetics, Bethesda, MD) and evaluated using the program Image ProExpress version 4.0 for Windows (Media Cybernetics).…”
Section: Methodsmentioning
confidence: 99%
“…The increased macrophage accumulation in the intestine and liver of GVHD mice observed previously in this work might be secondary to the production of CCL2, CCL3, and CCL5, which were observed in GVHD group, as these chemokines are known chemoattractants of macrophages and T cells. Macrophages can also produce such cytokines and chemokines to perpetuate the inflammatory process observed in GVHD [29,30,31,32,33,34,35,36,37]. Previously, our group reported that intestinal CCL2 levels were increased from the early stages of GVHD [35].…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages can also produce such cytokines and chemokines to perpetuate the inflammatory process observed in GVHD [29,30,31,32,33,34,35,36,37]. Previously, our group reported that intestinal CCL2 levels were increased from the early stages of GVHD [35]. Moreover, the interaction of CCL2 with its receptor facilitates the activation and migration of CD8 + T lymphocytes to GVHD target organs [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p100g is required for optimal T-cell activation [162]. Inhibitors targeting p100g/d consequently have potential utility in hematological malignancies (e.g., chronic lymphocytic leukemia [163]), inflammatory disease (e.g., asthma [164], arthritis [160]) and as immunosuppressives during organ transplantation [165].…”
Section: Pi3k/mtor/aktimentioning
confidence: 99%